Mathematical mapping analysis method of multi-power system coupled with planetary gears - GUI Jingliang; JIA Yanyan; REN Wei; PAN Zhenfeng; ZHANG Rongbin (Jixie chuandong)
ObjectiveIn order to quantitatively work out operating parameters and relation of parts of multi-power system coupled with planetary gears, a mathematical mapping analysis method was proposed.MethodsThe method was discussed by analyzing the hybrid system coupled with planetary gears of one truck, the kinematic and mechanical relations of parts of the system were deduced; a mathematical map was constructed with Matlab software; the switching order of modes and the path planning in start-up acceleration were quantitatively analyzed; the optimal cruising fuel consumption under different slopes and speeds was quantitatively analyzed; based on the above analysis, three system architecture optimizations were proposed, and compared to the original system in performance with simulation.ResultsThe switching order of modes, the path planning and the optimal fuel consumption point under cruising conditions could be intuitively and quantitatively figured out. The optimizations are verified by simulation to have a certain effect in performance improvement, which is useful for the development of control strategy and calibration of the system.